MANAJEMEN EKSTRAKURIKULER DALAM MENDUKUNG PROFIL PELAJAR PANCASILA - SAM, Mu'arif; Faizah; Mardya, Salwa Nabila; Reksha Azrie Ghibra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The management of extracurricular activities plays a vital role in supporting the implementation of the Pancasila Student Profile, as it serves as a vehicle for the holistic development of students' character, skills, and competencies. Well-planned, organized, directed, and sustainable extracurricular management can optimize the achievement of the six dimensions of the Pancasila Student Profile. This study aims to analyze the management of extracurricular activities in supporting the implementation of the Pancasila Student Profile through a review of relevant literature. A qualitative method with a literature review approach was employed in this research. Data sources were derived from national and international journals, books, government regulations, and various scientific documents related to extracurricular management and the Pancasila Student Profile. Data analysis was conducted through the processes of identification, selection, categorization, synthesis, and interpretation of findings from various sources. The synthesis results indicate that the successful implementation of the Pancasila Student Profile is influenced by extracurricular management encompassing program planning, resource organization, character-oriented activity execution, and continuous evaluation. Extracurricular activities are also proven capable of developing students' values of mutual cooperation, independence, creativity, critical reasoning, global diversity, as well as faith and noble character, provided they are supported by collaboration among schools, teachers, parents, and the community. Consequently, effective extracurricular management constitutes a crucial strategy in fostering students whose character aligns with the Pancasila Student Profile.